a solução, em reais, da inequação produto a seguir é igual a: (x-5) (-x+3) (2x+4) < ou igual a 0
Respostas
respondido por:
1
(x-5)*(-x+3)*(2x+4) ≤ 0
(x-5)*(-1)*(x-3)*2*(x+2) ≤ 0
(x-5)*(x-3)*(x+2) ≥ 0
q=x-5 ==>q------------------------(5)++++++++++++++++
p=x-3 ==>p----------------(3)+++++++++++++++++++++
s=x+2 ==>s--------(-2)+++++++++++++++++++++++++
Estudo de Sinais:
q--------------------------------(5)++++++++++++++++
p---------------------(3)+++++++++++++++++++++
s---------(-2)+++++++++++++++++++++++++
qps-----(-2)++++(3)-------(5)++++++++++++++++++++
[-2,3] U [5,+∞) é a resposta
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás